19. EVALUATION FOR THE ANTIBACTERIAL AND ANTIFUNGAL ACTIVITIES IN VITRO AND IN SILICO OF SYNTHESIZED IMIDAZOLE-4,5-DICARBOXAMIDE DERIVATIVES (Vietnam Journal of Community Medicine, 2024)
Objectives: Imidazole-4,5-dicarboxamide (I45DC) bearing the morpholine group has shown many diverse biological activities. The study aimed to further evaluate the antibacterial and antifungal activities of this group of compounds, using the in silico methods to interpret the results.Methods: Method for testing antibacterial and antifungal activities in vitro: agar diffusion methods. Method for evaluating in silico antibacterial and antifungal activities include building 10 molecular docking models, evaluating the models using the redocking method, docking synthesized substances into 10 models and evaluating based on docking score. Pharmacokinetic and toxicological properties (ADMET) were evaluated using ADMETlab2.0 software.Results: The synthesized substances did not show antibacterial or antifungal activities on the tested bacterial and fungal strains. In silico results showed that 10 substances were successfully docked to 10 common targets of bacteria and fungi. ADMET results showed some of the compounds are insoluble and cytotoxic.Conclusions: The in silico results were not consistent with the in vitro results. This may be explained by the fact that the test substances may not form important interactions with the targets or due to poor solubility.
Keywords: imidazole-4,5-dicarboxamide; antibacterial activity; antifungal activity